La bande dessinée française en Hongrie à la fin de l’ère kadarienne : l’exemple du magazine trimestriel Hahota - Kiss, Ádám László (Acta Romanica Quinqueecclesiensis : La publication du Département d'Études Françaises et Francophones, Université de Pécs, 2025)
The Western European comics were represented in the socialist Hungary mainly by the bandes dessinées of the French publishing house Éditions Vaillant. The main shareholder in Vaillant being the French communist party, the comics were provided to Hungarian youth periodicals free of charge. Early in the last decade of the declining Kádár-era, in 1980, a youth humour magazine named Hahota was launched of which an essential part was the comics strips of Vaillant. From 1986, other Western comic magazines started to be published, a process that accelerated further from 1990, leading to the closure of those magazines that had been publishing Vaillant comics strips, including Hahota. This essay examines the numbers of Hahota published between 1980 and 1989, focusing on the French comic strips that appeared in them.